HYBRIDITY AND MIMICRY ON THE MAIN CHARACTER IN ABDOEL MOEIS’S SALAH ASUHAN - Riki Pradana Putra (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to describe the form of Hybridity and Mimicry shown by the main characters in the analyzed novel. This research is descriptive qualitative. The data of this research are in the form of quotes, phrases, sentences, and paragraphs that reveal the contents of the story in the novel. The data source in this study is the novel Salah Asuhan by Abdoel Moeis published by PT. Balai Pustaka in 2006. The approach used is the study of Postcolonial Hybridity and Mimicry Homi K. Bhabha. The results of this study indicate that the first, the hybridity shown by the main character, in this case the Hanafi character in the novel Salah Asuhan, is the Hanafi character's attempt to mix Dutch identity into his Malay identity in the Minangkabau traditional environment with the aim of building a mindset of style progress. living in an environment of the Malay nation which he considered far behind from European civilization. Second, apart from the form of hybridity, there is a form of mimicry shown by the Hanafi character in Abdoel Moeis's novel Salah Asuhan in the form of imitation of attitudes, ways of dressing, customs and customs of Europeans, especially the Dutch into themselves who are actually Malay Natives who consider that the status of the nation is Europe is higher than the status of the Malay nation.